2022
DOI: 10.3389/fimmu.2022.798022
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis Reveals a Distinct Neutrophil Extracellular Trap-Associated Regulatory Pattern

Abstract: BackgroundNeutrophils form extracellular net-like structures called neutrophil extracellular traps (NETs). Emerging evidence has shown that cancer can induce NET formation; however, it is not fully understood how NETs influence cancer biology, and no consensus has been reached on their pro- or antitumor effects. A comprehensive analysis of the global NET-associated gene regulatory network is currently unavailable and is urgently needed.MethodsWe systematically explored and discussed NET enrichment, NET-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Neutrophils within the TME, which are known to form extracellular traps (NETs), have been shown to exert a complex regulatory capacity in many types of cancer. We have also found that increased neutrophils and NETs promote HCC growth and progression by provoking a tumorous inflammatory response [ 12 , 20 ]. In the present study, the enrichment of NETs was further observed in ECM score-high HCC (Additional file 4 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils within the TME, which are known to form extracellular traps (NETs), have been shown to exert a complex regulatory capacity in many types of cancer. We have also found that increased neutrophils and NETs promote HCC growth and progression by provoking a tumorous inflammatory response [ 12 , 20 ]. In the present study, the enrichment of NETs was further observed in ECM score-high HCC (Additional file 4 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular function analysis of 134 copper related genes was conducted via the ClueGo application in the Cytoscape software [ 34 ]. Gene set variation analysis (GSVA) of the 14 copper metabolism-related pathways in HCC and corresponding normal liver samples was performed by the ‘GSEABase’ and ‘GSVA’ packages in R software [ 35 ]. GSEA of CMscore-based classification of HCC patients was performed as described in our previous works [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…These NETs, intricate network structures resulting from the release of chromatin outside the cell through a specialized death pathway, actively participating in various cellular processes. 31 The role of exosomes in inducing NETs formation has been firmly established across various diseases. 32 Macrophagederived exosomes stimulated by Ox-LDL can promote atherosclerosis by inducing the formation of NETs.…”
Section: Texs-induced Phenotypic Transformation Of Tan and Formation ...mentioning
confidence: 99%
“…Moreover, neutrophils can be stimulated by TEXs to form neutrophil extracellular traps (NETs). These NETs, intricate network structures resulting from the release of chromatin outside the cell through a specialized death pathway, actively participating in various cellular processes 31 . The role of exosomes in inducing NETs formation has been firmly established across various diseases 32 .…”
Section: Texs‐induced Phenotypic Transformation Of Tan and Formation ...mentioning
confidence: 99%